2010
DOI: 10.3324/haematol.2009.017103
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical and pharmacokinetic study of a novel schedule of flavopiridol in relapsed or refractory acute leukemias

Abstract: BackgroundA pharmacokinetically derived schedule of flavopiridol administered as a 30 min intravenous bolus followed by 4-hour continuous intravenous infusion (IVB/CIVI) is active in fludarabinerefractory chronic lymphocytic leukemia, but no studies examining the feasibility and maximum tolerated dose of this schedule have been reported in acute leukemia. Design and MethodsWe conducted a phase I dose escalation trial of single-agent flavopiridol in adults with relapsed/refractory acute leukemias, utilizing a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
9
37
0
Order By: Relevance
“…10,35 While clinical studies have demonstrated the safety of using transcriptional repressors such as flavopiridol and SNS-032 that inhibit Cdks and block Mcl-1 expression, the limited clinical activity observed in patients with leukemias suggests that targeting Mcl-1 alone may only be effective in a subset of AML cases. 45,46 Our findings show that dual targeting of both PI3K and transcriptional kinases by PIK-75 demonstrates antileukemic activity in primary human AML cells without impacting on the survival, colonyforming potential, or engraftment capacity of nontransformed hematopoietic BM progenitors ( Figure 6). Thus, while PIK-75 targets 2 fundamental cell survival pathways, our data indicate that there is a therapeutic window that permits selective targeting of AML cells.…”
Section: Discussionmentioning
confidence: 81%
“…10,35 While clinical studies have demonstrated the safety of using transcriptional repressors such as flavopiridol and SNS-032 that inhibit Cdks and block Mcl-1 expression, the limited clinical activity observed in patients with leukemias suggests that targeting Mcl-1 alone may only be effective in a subset of AML cases. 45,46 Our findings show that dual targeting of both PI3K and transcriptional kinases by PIK-75 demonstrates antileukemic activity in primary human AML cells without impacting on the survival, colonyforming potential, or engraftment capacity of nontransformed hematopoietic BM progenitors ( Figure 6). Thus, while PIK-75 targets 2 fundamental cell survival pathways, our data indicate that there is a therapeutic window that permits selective targeting of AML cells.…”
Section: Discussionmentioning
confidence: 81%
“…In our phase I trial of FLAM with escalating doses of 'hybrid' flavopiridol for adults with relapsed and refractory acute leukemias, 19 the maximal tolerated dose was 90 mg/m 2 (30 mg/m 2 bolus followed by 60 mg/m 2 infusion) daily for three days, which represents a 28% increase over the 70 mg/m 2 total dose daily for three days used in the present study. However, pharmacokinetic studies of haematologica | 2012; 97(11) flavopiridol given by bolus, 16,23,25 infusional, 23,24,34 or 'hybrid' 19,[26][27][28][29] schedules display significant inter-individual variability. This variability occurs for both total and unbound drug concentrations and, in the context of the 'hybrid' schedule, is independent of total serum protein, albumin, WBC or occurrence of flavopiridol-related toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…19 In order to mitigate imbalance in randomization, patients were stratified by presence or absence of secondary AML, antecedent MDS or MPD six months or more prior to AML transformation, and therapy for antecedent disorder. 29,30 As in previous FLAM trials, [16][17][18][19] a 72-h continuous infusion of ara-C 2 gms/m 2 (667 mg/m 2 /24 h) began Day 6 and mitoxantrone 40 mg/m 2 was administered as an intravenous bolus over 60-120 min on Day 9, 12 h after completing ara-C. Patients who achieved CR after cycle 1 were eligible to receive a second cycle of FLAM beginning 21±7 days following hospital discharge from the first cycle.…”
Section: Treatmentmentioning
confidence: 99%
“…The combinations of Xavopiridol with gemcitabine and irinotecan (Fekrazad et al 2010), vorinostat (Dickson et al 2010), oxaliplatin and Xuorouracil/leucovorin (Rathkopf et al 2009), paclitaxel and carboplatin (George et al 2008), cisplatin and carboplatin ) and irinotecan (Shah et al 2005) were also assessed in various solid tumors in phase I clinical trials. In leukemias, Xavopiridol both as single agent Blum et al 2010) and in combinations with 1-beta-D-arabinofuranosylcytosine and mitoxantrone (Karp et al 2005) and cytosine arabinoside and mitoxantrone (Karp et al 2011) showed a promise in phase I clinical trials.…”
Section: Broad-range Inhibitorsmentioning
confidence: 99%